Efektivitas Program Makan Gizi Gratis (MBG) Presiden Prabowo terhadap Kualitas Gizi dan Pendidikan para Siswa di Indonesia - Tuti Yelvianti (Poltekkes Kemenkes Padang, 2025)
Malnutrition and stunting remain major public health issues in Indonesia, particularly among school-aged children. The Free Nutritious Meal (MBG) program launched by President Prabowo Subianto in 2025 aims to address these problems while improving educational quality. This study aims to analyze the effectiveness of the MBG program on students' nutritional status and academic performance. A qualitative content analysis was conducted through a systematic literature review. Out of 4,930 articles identified, only four met the inclusion criteria. The findings indicate that the MBG program reduced the prevalence of stunting by 7.8% and anemia by 5.4% among elementary students. Additionally, student attendance increased by 12%, and learning concentration improved by 15%. However, several challenges remain, including limited food storage infrastructure, uneven distribution, and a lack of technical regulations. The program has shown a positive impact on student health and education. In conclusion, MBG holds significant potential as an effective national program if supported by strong governance. It is recommended that the government strengthen cross-sectoral coordination, develop standardized menus based on local needs, and ensure sustainable logistics and implementation oversight.